Effects of forest structure on woody plant diversity in an evergreen broadleaved forest in Cao Bang province - Minh Dung, Quoc; Thi Huong Ly, Nguyen; Anh Thanh, Le; Van Quy, Nguyen (Journal of Forestry Science and Technology, 2023)
The present study was conducted in Phia Oac-Phia Den National Park in Cao Bang province to evaluate the interplay between forest structure and the diversity of woody plant species in an evergreen broadleaved forest. In six 1-ha permanent plots, all trees with a diameter at breast height (DBH) greater than 6 cm were identified, and their DBH, crown diameter, total tree height, and spatial coordinates were recorded. Spatial structure indices, non-spatial structure indices, and species diversity indices were utilized to construct a structural equation model (SEM). The results showed that the SEM model developed exhibited a good fit with CFI=0.98 and SRMR=0.02, signifying its accurate data modelling capabilities. The results emphasized the significant influence of both spatial and non-spatial structure on various woody plant diversity indices, including species richness, Shannon-Weiner diversity, Simpson diversity, and Pielou evenness. Notably, the horizontal spatial structure exerted a more pronounced effect on species diversity than the vertical structure. Furthermore, this study indicated a positive relationship between forest structure and diversity indices, highlighting their benefits. Conversely, interspecies competition negatively affected plant species diversity within the forest stands. This study provides a robust scientific foundation that supports effective strategies for the conservation and sustainable development of forest resources in the study area. It offers valuable insights for forest managers aiming to implement conservation and sustainability initiatives in the tropical evergreen broadleaved forest region.